Digital Literacy, Organizational Support, and Learning Community in Independent Teaching Platform towards Teacher Performance - Rosliani, Elis (Journal of Ecohumanism, 2024)
The aim of the research is to examine the influence of digital literacy, organizational support, and community learning in independent teaching platform on the performance of teachers. The research method used is quantitative with survey. The population in this study were all teachers of Senior High School at West Java Province, totaling 55.820 teachers. By using Slovin formulation with 10% of error degree, the research samples are 100. The researcher uses random sampling to determine the respondents to be sample of this research. The data collection technique uses a questionnaire with a Likert scale. The data analysis technique uses multiple regression using the SPSS Version 22 program. The research results are: 1. There is effect of digital literacy on the performance of teachers of Senior High School of West Java Province; 2. There is effect of organizational support on the performance of teachers of Senior High School of West Java Province; 3. There is effect of community learning in independent teaching platform on teachers of Senior High School of West Java Province; and 4. There are effect of digital literacy, organizational support, and community learning in independent teaching platform on the performance of teachers of Senior High School of West Java Province.